2023
DOI: 10.1108/imds-08-2022-0487
|View full text |Cite
|
Sign up to set email alerts
|

The complementary effect of ride-sharing on public transit: evidence from a natural experiment

Di Xu,
Ganxiang Huang,
Wei Zhang
et al.

Abstract: PurposeIdentifying the complementary effects of ride-sharing on public transit is critical to understanding the potential value of growing partnerships between public transit agencies and ride-sharing platforms. The purpose of this paper is to investigate whether and how ride-sharing services complement public transit.Design/methodology/approachTaking advantage of a natural experiment whereby subway Line 2 opened after the entry of ride-sharing services in Xiamen, this study uses a difference-in-differences ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(196 reference statements)
0
1
0
Order By: Relevance
“…This integration has been shown to boost PT ridership, reduce car ownership, and enhance service quality in both low-demand and urban areas [16,56]. Studies have demonstrated the potential of integrating SAVs with PT to create a more inclusive and efficient urban transportation network [8,57]. To evaluate and assess this complementary nature, recent studies have focused on the design of peer-topeer ride-matching systems for integrated PT services, highlighting innovative approaches to enhance urban mobility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This integration has been shown to boost PT ridership, reduce car ownership, and enhance service quality in both low-demand and urban areas [16,56]. Studies have demonstrated the potential of integrating SAVs with PT to create a more inclusive and efficient urban transportation network [8,57]. To evaluate and assess this complementary nature, recent studies have focused on the design of peer-topeer ride-matching systems for integrated PT services, highlighting innovative approaches to enhance urban mobility.…”
Section: Literature Reviewmentioning
confidence: 99%